Maritime navigation and radiocommunication equipment and systems. Global navigation satellite systems (GNSS). Navigation with Indian constellation (NavIC)/Indian regional navigation satellite system (IRNSS). Receiver equipment. Performance requirements, methods of testing and required test results Part 6, (10th March 2023) - British Standards Institution,
No abstract available